Strengthening Generation Z's Export-Import Competency through a Project-Based Collaborative Learning Model: An Islamic Law Perspective in the Era of Digital Transformation - Setyawan, Wawan Herry; Maulidia Zahrotus Sa'adah (VRISPRAAK : International Journal of Law, 2025)
The rapid pace of digital transformation has exacerbated the skills gap in the international trade sector, posing a significant challenge for Generation Z (Gen Z) entering the workforce. Traditional educational models often fail to equip them with the necessary technical, interpersonal, and strategic competencies. This research proposes the Project-Based Collaborative Learning (PBCL) model as an innovative pedagogical solution. However, from an Islamic law perspective, trade (tijarah) demands more than economic proficiency; it requires adherence to Sharia principles such as legality (halal), goodness (thayyib), and the avoidance of prohibited elements like usury (riba), uncertainty (gharar), and gambling (maysir). This study explores how the PBCL model not only enhances pedagogical effectiveness but also aligns with the higher objectives of Islamic law (Maqasid al-Shari'ah)—namely, the preservation of wealth (hifdz al-mal), the development of intellect (hifdz al-'aql), and the attainment of public benefit (maslahah 'ammah). By integrating Islamic business ethics (adab al-tijarah) into the curriculum, the PBCL model aims to cultivate a generation of Muslim professionals who are not only digitally savvy but also possess spiritual integrity and a sense of social responsibility in the global marketplace. Employing a qualitative descriptive approach, the study finds that the PBCL model significantly enhances Gen Z's competencies while simultaneously internalizing Islamic ethical values, making it a relevant and urgent framework for adoption in the digital era.